Analisis Keberlanjutan Perikanan Tuna Skala Kecil di Seram Selatan Kabupaten Maluku Tengah - Payapo, Muhammad Zia Ulhaq; Maitar, Bustar; Saragih, Mida; Attamimi, Gadri R. (Cenderawasih University, 2024)
Small-scale tuna fisheries have a considerable share in fishing production, especially in Maluku. The sustainability of small-scale tuna fisheries is expected to improve the condition of the resources and the fishing community itself. Tuna fishing activity in South Seram, Central Maluku Regency is one of the small-scale tuna fisheries activities. The declaration of a measured fishing program as an implementation of Law Number 11 of 2020 concerning Ciptakerja makes it necessary to conduct a study on the sustainability of tuna fisheries in the South Seram region to know the relationship between aspects and sub-aspects involved in small-scale tuna fisheries. The aspects and sub-aspects used refer to the theory of sustainable development: economic aspects, social aspects, ecological aspects, and governance aspects. This research uses path analysis analytical techniques used to analyze the causal relationship between variables that use the magnitude of the value. Data was obtained through interviews based on questionnaires. A sample of 135 people was taken purposively using the purposive sampling method. Based on the results of the study, it is known that the economic aspect has the greatest influence among the other three aspects with an influence value of 60.8%, social aspects of 29.2%, ecological aspects of 43%, and governance aspects of 35.1%. The most influential variable in the economic aspect is the income variable with an influence value of 23%. The most influential variable in the social aspect is the level of education with an influence value of 29.1%. The most influential variable in the ecological aspect is the impact on fish with an influence value of 41%. The most influential variable in the governance aspect is the understanding of measured fishing with an influence value of 17.9%.